Families and educational systems in sub-Saharan Africa (Foro de Educacion, 2012)
Studies and analysis of African educational systems’ performance do not pay much attention to the role of families; to the value they give to school and to how this may affect their decisions. By contrast, there are numerous researches focused on the most subjective elements of the relation between families and school: the attitudes, meanings and representations families, separately or as members of a social class or ethnic group, have of school. In this paper we will give five examples, drawn on sociological and anthropological studies, of different schooling practices and family representations of school. These are examples situated in different contexts and geographical areas that will allow us to appreciate the level of heterogeneity of family-school relationships in Africa and that may contribute to make us think otherwise the evolution of these educational systems.